2002
DOI: 10.1007/s00330-002-1368-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-dose and standard-dose helical CT in the evaluation of pulmonary nodules

Abstract: The purpose of this study was to investigate the diagnostic accuracy of low-dose helical computed tomography by comparing the number of nodules detected at low-and standard-dose CT. The prospective study included 25 patients who were referred to CT scan for the assessment of pulmonary metastases. All patients underwent CT examinations at both standard-(200 mA, 120 kV, collimation 5 mm, table feed 10 mm per rotation) and low-dose (50 mA, 120 kV, collimation 5 mm, table feed 10 mm per rotation). The number of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…There are several investigations on the radiation dose reduction for specific abnormal findings including pulmonary nodules [9], [10], emphysema severity [11], [12], [13] and bronchiectasis [14]. There are also several studies on the radiation dose reduction for CT pulmonary angiography [15], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…There are several investigations on the radiation dose reduction for specific abnormal findings including pulmonary nodules [9], [10], emphysema severity [11], [12], [13] and bronchiectasis [14]. There are also several studies on the radiation dose reduction for CT pulmonary angiography [15], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…The application of low dose CT technique has been facilitated by various techniques, including automatic exposure systems and imaging filters [13], [14], [16], [17], [18], [19], [20]. As chest CT examinations are frequently used for lung lesion detection, detection of lung nodules using low dose CT images has been investigated by several groups [1], [2], [3], [4], [5], [21]. These results showed that detection of pulmonary nodules is possible with low dose CT images obtained with 20–50 mAs.…”
Section: Discussionmentioning
confidence: 99%
“…Low dose CT examinations are currently employed to detect lung nodules and to find treatable lung cancer cases [1], [2], [3], [4], [5], [6], [7], [8]. Low dose CT is much more effective as a screening process than chest X-ray, but the drawback is that low dose CT examinations uncover many nodules or larger localized lesion which should be differentiated from lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, quantum noise increases inversely in proportion to the square root of the amperage. However, because the lungs are aerated, they generate more contrast than solid organs, and the detection of pathological changes in the lung are less dependent on image noise than for those in solid organs (3). …”
Section: Discussionmentioning
confidence: 99%
“…Although low- to ultra-low-dose chest CT has been used, conventional 50 mA low-dose CT is normally used for lung cancer screening (3, 6, 13). Moreover, previous studies on low-dose or ultra-low-dose CT were performed without a CAD system (3, 5, 6, 13), and no comparative information is available in the English language clinical literature on low-dose and ultra-low-dose CT supported by a CAD system. In the present study, we assessed the rationale and feasibility of the use of ultra-low-dose helical CT using a CAD system.…”
mentioning
confidence: 99%